THE INTEGRATION OF SECOND CORE COMPETENCE (KI 2) OF CURRICULUM 2013 IN ENGLISH CLASSES (ELT Forum: Journal of English Language Teaching, 2015)
This final project is based on a study which attempted to describe the integration of character education in a real teaching. The main purpose of the study was to describe how the teachers integrated and assessed (KI 2) or character education to their students in English classes. Three english teachers from two different school levels participated in this research. They taught their students in the class. From the teaching and learning process, the transcriptions which contained teachers’ acts and talks was provided. Then, both teachers’ acts and talks were displayed on a table. They were categorized based on 18 pillars of character education which is proposed by Kemendiknas. After both teachers’ acts and talks were categorized, the researcher explained what methods or strategies were used in integrating and assesing character education. After that, the researcher summarized all the findings from the data and conclude them. Results indicated that all the three teachers who became the source of data have already integrated character education in their class. The first teacher or teacher A integrated discipline and social care. Both discipline and social care are displayed twice on the transcription. The next teacher is teacher B. During her class, she integrated tolerance three times, respect of the achievement three times, social care four times, each democratic, communicative and discipline one time to all her students. The last teacher is teacher C. She did integrate curiosity once, religious for four times and both tolerance and democratic twice. Charater education has already integrated by all teacher in each class. There was no new strategy which was used by all the teachers in integrating character education. The strategies which were mostly used by the teachers were only in the form of advice. In addition, there was no strategy which was used by the teachers to assess character education. This could happen because the teachers did not do any single assessment to character education which they have transferred on that day.